A new species of four-eyed frog genus Pleurodema Tschudi, 1838 (Anura: Leiuperidae) from the rock meadows of Espinhaço range, Brazil - Maciel, Daniel Bastos; Nunes, Ivan (Zootaxa, 2010)
A new Brazilian species of Pleurodema, closer to Pleurodema diplolister (Peters), from the Brazilian rock meadows (Campos Rupestres) is described. This new species is characterized by the following combination of traits: medium size (males 32.3–36.1 mm SVL); lumbar gland absent; tarsal fold absent; presence of a tarsal tubercle near the heel; inner metacarpal tubercle rounded and well developed in males; supernumerary tubercles on hand absent or vestigial; annulus tympanicus distinct; absence or vestigial presence of fringes in fingers; and absence of flash coloration in the hidden portions of the thighs and groin.